Photodegradation in terrestrial ecosystems - Austin, Amy Theresa (2024)
The ﬁrst step in carbon (C) turnover, where senesced plant biomass is converted through variouspathways into compounds that are released to the atmosphere or incorporated into the soil, istermed litter decomposition. This review is focused on recent advances of how solar radiation canaffect this important process in terrestrial ecosystems. We explore the photochemicaldegradation of plant litter and its consequences for biotic decomposition and C cycling. Theubiquitous presence of lignin in plant tissues poses an important challenge for enzymatic litterdecomposition due to its biological recalcitrance, creating a substantial bottleneck fordecomposer organisms. The recognition that lignin is also photolabile and can be rapidly alteredby natural doses of sunlight to increase access to cell wall carbohydrates and even bolster theactivity of cell wall degrading enzymes highlights a novel role for lignin in modulating rates oflitter decomposition. Lignin represents a key functional connector between photochemistry andbiochemistry with important consequences for our understanding of how sunlight exposure mayaffect litter decomposition in a wide range of terrestrial ecosystems. A mechanistic under-standing of how sunlight controls litter decomposition and C turnover can help informmanagement and other decisions related to mitigating human impact on the planet.